1997
DOI: 10.1111/j.1442-200x.1997.tb03595.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of juvenile dermatomyositis in Japan

Abstract: Questionnaires were sent to 1290 hospitals in Japan asking for data on patients with juvenile dermatomyositis (JDM) diagnosed between June 1984 and May 1994. Of the 204 patients identified by these questionnaires, 102 met the criteria for JDM. JDM is categorized into three subtypes: Banker-type JDM, Brunsting-type and fulminant-type; patients with the latter exhibit markedly elevated serum levels of creatinine phosphokinase ( > 10 000 U/mL) and appear to be at risk of renal failure. Cutaneous manifestations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
2
9
3
Order By: Relevance
“…We also found that calcinosis and pain were related to higher CHAQ scores. Again, this result is not surprising, and is consistent with data reported by other investigators (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%
“…We also found that calcinosis and pain were related to higher CHAQ scores. Again, this result is not surprising, and is consistent with data reported by other investigators (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%
“…The frequency of ILD in JDM has been reported to be low in comparison with that in adult DM. [9][10][11] However, the report by Kobayashi et al 6 indicated that the frequency of ILD seems to be high in our study (Table 3). These results might be associated with the severity of the disease, and recent advances in such diagnostic modalities as CT scans and serum KL-6, or Japanese ethnogenesis, e.g., human leukocyte antigen molecules and genes.…”
Section: Discussioncontrasting
confidence: 56%
“…The positive rates for EMG and muscle biopsy in JDM with muscular signs have been reported to be 60%-100% and 90%-100%, respectively, 9,11 and they have thus been established as a valuable tool for the diagnosis of JDM. 15,16 In recent MRI studies, fat-suppressed MRI made it easy to identify the muscular, cutaneous, subcutaneous, and fascial changes in the early disease course.…”
Section: Discussionmentioning
confidence: 99%
“…ILD occurs after the diagnosis of polymyositis or dermatomyositis in up to 40% of patients, and precedes the diagnosis of overt CTD in 20-30% of cases [47,52]. In large cohorts of JDM/JPM, ILD occurs in 8-13% of patients and thus seems to occur less frequently than in adult dermatomyositis [53,54]. Risk factors for ILD in a patient with dermatomyositis/polymyositis include genetic predisposition [55,56], some clinical signs such as arthralgia [47], and autoimmune features (table 2) [22,56,57].…”
Section: Direct Pulmonary Involvementmentioning
confidence: 99%